Implementation Learning Based Project To Creativity Study PPKn Class X SMAN 14 Medan - Ma'wa, Camelia Khuznul; Susilawati, Evi; Gultom, Rumesti (Jurnal Akuntansi Hukum dan Edukasi, 2024)
Writing work scientific aim count influence implementation learning with a project focus to improvement creativity Study student in class X at SMAN 14 Medan. Study This started from background behind problem ie exists problem learning happens in the classroom so that hinder the learning process teaching, As for the problem the is students are less open to input where students are reluctant to change bad habits such as picking on friends, being noisy in class and not paying attention to the teacher, then students are less creative in answering questions, the average answer they say and write is the same answer and monotonous, students are less having a sense of responsibility for what is done and no lack of a sense of independence dominates the classroom, where there are only a few students who are able to complete challenges uniquely and uniquely and the rest only look at and follow the answers in book language, so that the answers given tend to be the same. This problem refers to a lack of student creativity because it shows creativity indicators. The low level of student learning creativity means that students are limited in developing themselves, this is because they do not feel the freedom of expression, so solutions must be immediately provided so that learning can take place optimally. Researchers provide a solution in the form of implementing a project-based learning model so that students are free to provide and express unique and unique ideas with supervision and guidance from the teacher. This research uses a quantitative approach with systematic data presentation regarding the assessment of statistical figures which are presented objectively and straightforwardly so that the results obtained are a real picture in the field and not the result of the researcher's subjectivity. The type of research method used is classroom action research or PTK which is carried out in two cycles, where the first cycle is carried out as a solution to problems that have not been resolved in the first cycle. Each cycle is carried out with two meetings. Classroom action research is carried out through four stages, namely the planning stage, action implementation stage, observation and reflection. The subjects in this research were students of class X IKM 5 SMAN 14 Medan with a total of 38 students in one class unit. The results in this research are with results observation about mark creativity Study student so found that's it giving action on the cycle First Not yet find maximum results and not yet passed the graduation limit namely 75%. So that researcher must carry out study cycle second. There are problems that must be solved repaired and found in implementation cycle First is a teacher lacking provide stimulus, too much explanation fast, and giving problem in missing projects concrete so that give rise to interpretation double by participants educate and collaborate group Still in threshold value 55-70 where mark the Still classified to category low value, problems in cycle I create Work The same in group less than optimal and adequate so that must given improvements to the cycle furthermore. exists significant improvement about implementation learning based project to creativity Study PPKn student Where show the average figure was 83% at meetings First with status from not enough become OK, then on to the meeting both also experienced high increase ie of 88% which shows already in category completeness and visibility Work The same in group experience increase Where the average level obtained initially only by 60% increase to 80-85%. So that can concluded that increase the show there is good influence in application of learning models based project in improvement cooperation participant educate in group.